PENGUATAN KARAKTER RELIGIUS BERBASIS BUDAYA SEKOLAH DI SMP MUHAMMADIYAH TOBOALI BANGKA SELATAN - Yolanda Augita; Dikdik Baehaqi Arif (Academy of Education Journal, 2022)
Character education in Indonesia is increasingly being eroded by the progress of the times. Therefore, it is very important to implement character education in Indonesia as an effort to give good habits to students. The purpose of this study was to determine the implementation of strengthening the religious character of students based on school culture at SMP Muhammadiyah Toboali, South Bangka Regency. This study uses a qualitative research type. Data collection techniques were carried out by interview and documentation. The results showed that 1) SMP Muhammadiyah Toboali applied the five main character values ​​of PPK. 2) Religious character becomes the flagship PPK program in schools. 3) There are obstacles in the implementation of strengthening the religious character of students, both constraints from the students themselves and constraints from limited time and facilities from the school. 4) The solution in dealing with these obstacles is to establish cooperation between the school and parents to fortify students to always carry out religious activities.